Description of a new species of Sabellidae (Polychaeta, Annelida) from fresh and brackish waters in Europe, with some remarks on the branchial crown of Laonome - Bick, Andreas; Bastrop, Ralf; Kotta, Jonne; Meißner, Karin; Meyer, Maria; Syomin, Vitaly (Zootaxa, 2018)
In 2009, a hitherto unknown Laonome species was found in the Canal Ghent-Terneuzen in the Netherlands and subsequently in other Dutch rivers, canals and estuaries. A few years later, more unknown Laonome specimens were found in the eastern part of the Baltic Sea and in the Don River estuary, Sea of Azov. Initially, it was assumed that these specimens could represent Laonome calida Capa, 2007, originally described from Australia. In the present study we examine all these unknown European Laonome specimens and compare these specimens with the type material of L. calida from Australia. This lead to two main results: First, all specimens from Europe have the same diagnostic characters and therefore belong to one species. This finding was also supported by the results of a correspondence analysis, and genetic analyses using four different DNA sequences (COI, 16S, 28S). Second, it turned out that the type material of L. calida contains two morphologically distinct groups of specimens. The holotype and 7 paratypes are similar to each other but differ significantly from the other also similar 16 paratypes, and from all European specimens. On the basis of these observations, the Laonome specimens from European waters are described here as L. xeprovala sp. nov. We also provide the characters of the branchial crown of three Laonome species for a prospective revision of this genus.